Evaluation of intersectoral resources in the composition of care networks for crack users - Leandro Barbosa de Pinho; Christine Wetzel; Jacó Fernando Schneider; Agnes Olschowsky; Marcio Wagner Camatta; Eglê Rejane Kohlrausch; Elitiele Ortiz dos Santos; Adriane Domingues Eslabão (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To evaluate the intersectoral resources in the composition of care networks for crack users. Method: Evaluative, qualitative study based on the Fourth Generation Evaluation. The participants were 10 users, 11 family members, eight workers, and seven managers from a municipality in the metropolitan region of Porto Alegre/Rio Grande do Sul, Brazil. Data were collected in 2014 through observation and semi-structured interviews. The analysis occurred by the constant comparative method. Results: Stakeholders have discussed how the Public Prosecutor's Office and the Military Brigade are inserted in the network, since they carry out actions that often are not compatible with the psychosocial care proposal. The need for expansion and maintenance of liaisons with community resources was identified. Conclusion: It is noted the need for sector integration and participation of all social agents from different spheres in order to promote and evaluate the practices and policies of care for crack users.